Colostrum-Derived Exosomal Lactoferrin Promotes Skin Fibroblast Regeneration by Suppressing Inflammatory Responses - Chu-Hsun Cheng; Wei-Jer Hong; Chien-Nien Li; Yung-Hsueh Huang; Jeng-Haw Tsai; Chih-Yuan Huang; Jen-Chin Wu; Chan-Yen Kuo; Wen-Chun Kuo (Current Issues in Molecular Biology)
Lactoferrin (LF), a multifunctional glycoprotein found abundantly in bovine colostrum, is known for its regenerative and anti-inflammatory properties. In this study, we investigated the wound healing and immunomodulatory effects of colostrum-derived exosome-encapsulated lactoferrin (EV-exoLF) on dermal fibroblasts. EV-exoLF was isolated and characterized via nanoparticle tracking analysis and flow cytometry. Functional assays demonstrated that EV-exoLF significantly promoted fibroblast viability and migration in both mouse NIH/3T3 and human HS-68 cell lines. Furthermore, EV-exoLF reduced the expression of pro-inflammatory cytokines (IL-1 and IL-6) and phosphorylated JNK in lipopolysaccharide (LPS)-treated fibroblasts. These findings suggest that EV-exoLF not only enhances fibroblast-mediated wound closure but also mitigates inflammation, highlighting its therapeutic potential in skin regeneration. Colostrum-derived exosomal lactoferrin may serve as a promising natural, cell-free strategy for managing inflammatory skin conditions and improving wound healing outcomes.